Acute aerobic exercise: an intervention for the selective visual attention and reading comprehension of low-income adolescents - Tine, Michele (Frontiers in Psychology, 2014)
There is a need for feasible and research-based interventions that target the cognitive performance and academic achievement of low-income adolescents. In response, this study utilized a randomized experimental design and assessed the selective visual attention (SVA) and reading comprehension abilities of low-income adolescents and, for comparison purposes, high-income adolescents after they engaged in 12-minutes of aerobic exercise. The results suggest that 12-minutes of aerobic exercise improved the SVA of low- and high-income adolescents and that the benefit lasted for 45-minutes for both groups. The SVA improvement among the low-income adolescents was particularly large. In fact, the SVA improvement among the low-income adolescents was substantial enough to eliminate a pre-existing income gap in SVA. The mean reading comprehension score of low-income adolescents who engaged in 12-minutes of aerobic exercise was higher than the mean reading comprehension score of low-income adolescents in the control group. However, there was no difference between the mean reading comprehension scores of the high-income adolescents who did and did not engage in 12-minutes of aerobic exercise. Based on the results, schools serving low-income adolescents should consider implementing brief sessions of aerobic exercise during the school day.